The use of operational cash flow in the estimation of accrual-based earnings management - Comporek, Michał (Wykorzystanie operacyjnych przepływów pieniężnych w estymacji zarządzania zyskiem, 2019)
One of the most important analytical spheres enabling the diagnostic estimation of intentional changes in a company’s financial result is the area of accrual adjustments of net profit, separated in the cash flow statement prepared using the indirect method. The special cognitive value of accrual differences can be seen when the structure of total accruals is separated by those adjustments that are not directly related to the real activity of the enterprise, and are the result of subjective accounting choices. The main objective of the article is to present the selected econometric models used for examining accrual-based earnings management phenomenon in Poland. The analysis includes following regression models, namely: the Jones model, the Kasznik model, the Dechow-Dichev model and the McNichols model. The empirical studies were conducted among listed companies qualified for the Warsaw Stock Exchange indices: WIG-20 and mWIG-40, whose shares were traded for at least ten years in 1998-2017
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 2, s. 46-60
Keywords: accrual-based earnings management; operational cash flow; net income; regression models; operacyjne przepływy pieniężne; korekty zysku netto; zarządzanie ryzykiem; wynik finansowy; modele regresji